Structural Characteristics of Family Educational Investment under Policy Reform: A Case Study of "Double Reduction"Policy in Inner Mongolia, China - Yan, Xiaochen (Technium Social Sciences Journal, 2025)
Family educational investment refers to the allocation of financial, temporal, and emotional resources by families to support children’s education and holistic development. This study examines the structural characteristics of family educational investment under China’s "Double Reduction" policy through a mixed-methods approach, utilizing data from 5,967 families in Inner Mongolia. Findings indicate a general decline in such investments, with disparities based on family income and children’s educational stages. Emotional investment is the most vital part of the educational production process. Mothers, particularly younger and more educated ones, assume a predominant role, while multi-child families face intensified burdens. The study identifies key patterns, including the reshaping of investment by educational anxiety, polarization of behaviors, and conflicts between family practices and teacher roles. Recommendations are proposed at family, school, and societal levels to optimize educational investments under the policy.